Um estudo sobre julgamentos e escolhas: vieses e heurísticas no processo de decisão dos regimes próprios de previdência social - Sandoval, Daniel Boueres (2016)
Up to the middle of last century, the theoretical framework of finance was mostly dominated by approaches that considered the investors, in their decision-making role, as rational agents gifted with unshakable uprightness, at the same time that saw the prices of the assets as nothing more than the results of the decisions taken by these agents, as they made use of all the information available in the market. The way these agents played their role, based on their aversion to risk and counting on a full view of their portfolio every time a decision had to be made, aimed at maximizing utility. The aim of this dissertation is to show, by means of a broader approach of finances and economics aligned with concepts of psychology and sociology, how agents, more particularly investors, are susceptible to rationality deviations that impact directly their choices, conflicting with the fundamentals of classical finance theories. As a consequence, investors do not always make their judgments and their choices in a way to avoid risk, with a consolidated view of their portfolio and with an aim at maximizing utility. The research was made with investors of the Brazilian Social Security Regimes, relevant to the country's present scenario, since expenses with social security is a key factor for striking a balance in the domestic budget and, consequently, for the sustainable growth of the country.